Blood chemistry and hematology of gray seal (Halichoerus grypus) pups from birth to postweaning - Hall, A J (1998)
Serum and plasma samples were collected from 92 gray seal (Halichoerus grypus) pups, all less than 5 wk old, and from 21 yearlings during the breeding season at the Isle of May, Firth of Forth, Scotland, for hematologic and clinical chemistry analysis. In the pups, total WBC, total protein, and glucose values increased until weaning and declined during the postweaning fast. Liver enzymes, particularly alkaline phosphatase, were high at birth and decreased steadily with age, most rapidly during the postweaning fast. In the yearlings, total WBC, erythrocyte sedimentation rates, and rectal temperatures were significantly higher than in the pups and glucose levels were significantly lower. Therefore, consideration should be given to the growth phase of gray seal pups (lactation or postweaning fast) or stage of development when hematology and clinical chemistries are used far diagnostic purposes.